Effect of band bending on topological surface transport of Bi2Te3 single crystal. (30th December 2020) - Kumar, Devendra; Lakhani, Archana
Abstract: Understanding the effect of surface to bulk coupling on topological surface states is important for harnessing the topological insulators for low dissipation electronics and quantum technologies. Here we investigate this effect on a low bulk carrier density Bi2 Te3 single crystal using magnetoresistance, Hall resistivity, and Shubnikov–de Haas oscillations. Our results show the presence of high mobility surface bands and low mobility bulk bands. The surface states exhibit ambipolar transport without any gating. The mobility of surface states strongly depend on the nature of band bending, the upward band bending with holes as surface charge carrier exhibit large mobility while the downward band bending with electrons as surface charge carriers exhibit low surface mobility. The large mobility of surface Dirac holes is related to low surface defect density and small cyclotron mass. We also observe large magnetoresistance ∼285% due to multichannel quantum coherent transport in the bulk.